Torsion of in-utero fetal ovarian cyst - Balasubramanian, Kruthiga Kumari; Natarajan, Lalitha; Arunachalam, Paavi; Maheshwari, Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A 22 years old primi-gravida was diagnosed to have a 6.3×5×5.37 cm hemorrhagic gonadal cyst in fetus at 38 weeks of gestation by growth scan, on follow-up. At term gestation, she delivered a female baby by vacuum assisted vaginal delivery, weighed 2.86 kg, no other anomalies. X-ray done at 1st hour of life showed mass on the right side. USG abdomen done showed an intraperitoneal cystic lesion (5.7×3.9×6.3 cm) in right lumbar quadrant of abdomen and pediatric surgeon was consulted. Baby taken for diagnostic laparoscopy on second day of life. Findings were right large ovarian cyst with torsion with adhesions to small bowel. 75 ml of hemorrhagic fluid drained and ovarian cystectomy done, sample sent for histopathological examination, turned out to be a simple cyst. Baby discharged on day 7 of life (POD-5), hemodynamically stable and on direct breast feeding, tolerated well.